Pengaruh Terpaan Media Sosial Twitter Terhadap Kepekaan Sosial Remaja di Kota Denpasar (Studi Pada utas “Twitter Please do Your Magic”) - Putri Utari, Nyoman Larashati; Purnawan, Ni Luh Ramaswati; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2021)
In this global era, social media has become part of people's daily lives, Twitter as an example. Twitter's popularity has increased since 2018, and a trend has emerged for the use of